Amazonia and the Anthropocene: What was the spatial extent and intensity of human landscape modification in the Amazon Basin at the end of prehistory?. (October 2015) - Piperno, Dolores R; McMichael, Crystal; Bush, Mark B
The nature and spatial scale of prehistoric human landscape modifications in Amazonia are enduring questions. Original conceptions of the issues by archaeologists published more than 40 years ago posited little human influence because of putative environmental constraints. Empirical data accumulated more recently demonstrated dense, permanent settlements along major watercourses of the central and southern Amazon, and profound landscape alterations in seasonally flooded savanna regions of Bolivia. These results led some investigators to propose that most to all of Amazonia was heavily populated and modified before European arrival, and that prehistoric fires and forest clearing were of such a massive scale that post-Columbian reforestation was a significant contributor to decreasing atmospheric CO2 levels and the onset of the 'Little Ice Age'. Recent data generated from investigations of soils sampled from underneath standing terra firme forests in parts of the western Amazon indicate ephemeral ancient human occupation and little vegetation disturbance there. These issues are central to ongoing discussions surrounding the classification and timing of the Anthropocene, because a geological epoch proposed on the basis of profound human alteration of environments and considerations of when during the Holocene it should begin, require robust paleo-environmental and archaeological data from major, critically important zones such as the Amazon Basin. This paper reviews debates and existing information on prehistoric human influences in Amazonia, provides new data from the western Amazon, and attempts to arrive at reasonable conclusions based on the available empirical data.